Ten years after: Eastern Germany's convergence at a halt? - Margarethe Quehenberger (EIB Papers, 2000)
A decade after German unification and the establishment of monetary, fiscal and social union between Western and Eastern Germany (1), it is time to take stock of the economic convergence reached so far, and to assess the prospects for further productivity catch-up. These issues are naturally of keen interest to German taxpayers - who are well aware that high fiscal transfers to the New Länder will not decline as long as their productivity trails behind Western German levels and unemployment stays at about 20%. For economists the case of Eastern German convergence is of particular interest as a near text book example of the 'big bang' reform of a planned economy. Legal and institutional reform, price adjustment and integration into world markets were practically achieved overnight. Privatisation was rapid, and by early 1995, some 95% of Eastern German employees already worked in private enterprises (DIW et al., 1999). Because of the speed of this process, the pre-dominance of transition-related effects can be considered to have come to an end within a few years.
Keywords: 330; Entwicklungskonvergenz; Neue Bundesländer; Deutschland